Graphic representations of theoretical solutions in engineering geometry - Kusebaev, Уалихан (Рroblems of engineering and professional education, 2022)
The article deals with graphic images of imaginary points with coordinates in the form of complex numbers. The essence of imaginary solutions explaintd by the existence of imaginary additions. As an example, a one-parameter set of hyperbole, as the imaginary supplement given circle.